A HAT1‐DELLA signaling module regulates trichome initiation and leaf growth by achieving gibberellin homeostasis. Issue 3 (30th May 2021) - Tan, Wenrong; Han, Qing; Li, Yan; Yang, Feng; Li, Jiafeng; Li, Pengxu; Xu, Xiumei; Lin, Honghui; Zhang, Dawei
Summary: Trichome initiation and leaf growth are two critical developmental processes in the plant life cycle, which need to be optimized in accordance with developmental stage and immediate surroundings. To a large extent, this optimization is achieved by fine‐tuning of hormonal pathways, including the gibberellin (GA) pathway. However, the mechanism by which plants control GA homeostasis to optimize these two developmental processes is unknown. Here, we report that HAT1, a HD‐ZIP II transcription factor, negatively regulates GA‐mediated trichome initiation and cotyledon expansion. Both protein and transcript levels indicated that HAT1 was induced by GA, while an increased abundance of HAT1, in turn, was found to suppress GA biosynthesis and signaling, thus forming a regulatory negative feedback loop that controls GA homeostasis to fine‐tune trichome development and cotyledon expansion. We also found that HAT1 interacts with DELLAs, including GAI and RGA. GAI inhibits both protein stability and the binding activity of HAT1 to its target genes. Overexpression of HAT1 in della5 can completely suppress the enhanced trichome initiation and enlarged cotyledon of della5 . Our findings demonstrate that HAT1 functions as a critical repressor to regulate GA‐mediated trichome initiation and cotyledon growth; in addition, we describe a novel mechanism by which the plant regulates trichome initiation and cotyledon expansion through a HAT1‐DELLA regulatory module under various GA concentrations.